Geographical features planned migration of population in the North Caucasus and problems of adaptation - Ivan Alekseevich Soloviev (Наука. Инновации. Технологии)
In the study, based on the unique archival sources, provides a general description of the migration of the North Caucasus during the Soviet period (1920-1960-ies.). The content of the work consists the analysis of the geographical features of the planned migration to the North Caucasus on a regional level (subjects) and sectional area (the historical area, municipal districts). An important place in the study of the planned migration takes revealing territorial characteristics of migrants residence before moving to the North Caucasus. The study revealed the volume of migration planned in the area, as well as the dynamics of the migrants flow. This paper describes the ethnic structure of the resettlement stream. A key role in the research content given to the identification problems of natural-climatic and economic adaptation of settlers, and in case of immigrants considered a problem of their integration into the host community.